A Cdc42-regulated actin cytoskeleton mediates Drosophila oocyte polarization - Leibfried, Andrea; Müller, Sandra; Ephrussi, Anne (Development, 2013)
Polarity of the Drosophila oocyte is essential for correct development of the egg and future embryo. The Par proteins Par-6, aPKC and Bazooka are needed to maintain oocyte polarity and localize to specific domains early in oocyte development. To date, no upstream regulator or mechanism for localization of the Par proteins in the oocyte has been identified. We have analyzed the role of the small GTPase Cdc42 in oocyte polarity. We show that Cdc42 is required to maintain oocyte fate, which it achieves by mediating localization of Par proteins at distinct sites within this cell. We establish that Cdc42 localization itself is polarized to the anterolateral cortex of the oocyte and that Cdc42 is needed for maintenance of oocyte polarity throughout oogenesis. Our data show that Cdc42 ensures the integrity of the oocyte actin network and that disruption of this network with Latrunculin A phenocopies loss of Cdc42 or Par protein function in early stages of oogenesis. Finally, we show that Cdc42 and Par proteins, as well as Cdc42/Par and Arp3, interact in the context of oocyte polarity, and that loss of Par proteins reciprocally affects Cdc42 localization and the actin network. These results reveal a mutual dependence between Par proteins and Cdc42 for their localization, regulation of the actin cytoskeleton and, consequently, for the establishment of oocyte polarity. This most likely allows for the robustness in symmetry breaking in the cell.